2020
DOI: 10.2147/hiv.s231173
|View full text |Cite
|
Sign up to set email alerts
|

<p>Current Status Towards 90-90-90 UNAIDS Target and Factors Associated with HIV Viral Load Suppression in Kediri City, Indonesia</p>

Abstract: Introduction: In 2016, UN Member States committed to reduce new HIV infections to fewer than 500,000 annually by 2020, a 75% reduction compared with 2010, reduce AIDS-related deaths to fewer than 500,000 globally as a means of ending AIDS by 2030. The UNAIDS 2020 target is to have 90% of the people living with HIV know their status, 90% of the people living with HIV (who know their HIV status as positive) are already on ART treatment, 90% of people on treatment are virally suppressed. The objective of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…That HIV stigma is a major impediment to ART adherence is well established in the literature [ 9 , 13 , 39 ], as is the fact that HIV stigma in health care is highly prevalent and highly detrimental for PLHIV [ 40 , 41 , 42 , 43 ]. As such, our findings dovetail with previous studies reporting that stigma in any form hinders treatment adherence [ 3 , 11 , 27 , 30 , 31 , 32 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. PLHIV also often experience intersectional stigma or stigmatization due to multiple identities within marginalized groups (e.g., gender or sexual orientation) [ 60 , 61 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…That HIV stigma is a major impediment to ART adherence is well established in the literature [ 9 , 13 , 39 ], as is the fact that HIV stigma in health care is highly prevalent and highly detrimental for PLHIV [ 40 , 41 , 42 , 43 ]. As such, our findings dovetail with previous studies reporting that stigma in any form hinders treatment adherence [ 3 , 11 , 27 , 30 , 31 , 32 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. PLHIV also often experience intersectional stigma or stigmatization due to multiple identities within marginalized groups (e.g., gender or sexual orientation) [ 60 , 61 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, ART adherence among PLHIV in Indonesia is low [ 2 ]. In terms of the 95-95-95 targets, the UNAIDS data for 2021 indicated that, of the estimated 610.000 PLHIV in Indonesia, only 66% are aware of their HIV status, 26% on ART, and no 2021 data was available on viral suppression [ 3 ], but earlier data also showed very poor rates of viral suppression [ 4 , 5 ]. Clearly, Indonesia, as a whole, does not meet the 95-95-95 targets [ 6 ] despite efforts, such as the 2012 continuum of care government initiative (Layanan Komprehensif Berkesinambungan) [ 7 ] and regional activities, such as the governor of Jakarta having signed the Paris Declaration in 2015 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current study includes all individuals with high viral load, whereas the previous study includes only those who were on the first-line ARV regimen. On the contrary, this finding is greater than the finding reported in the studies done in Southwestern, Ethiopia (20.3%) [ 51 ], Harare, Zimbabwe (31.2%) [ 26 ], Mumbai, India (28%) [ 24 ], Kediri City, Indonesia (9.9%) [ 52 ], a worldwide systematic review (70.5%) [ 53 ], and meta-analysis done by WHO (46.1%) [ 21 ].…”
Section: Discussionmentioning
confidence: 66%
“…Huerga et al [13] reported higher values of 90-90-90 targets on women (79%-71%-93%) compared to men (68%-68%-92%) on the South Africa population from Mbongolwane, Eshowe, and KwaZulu-Natal provinces. The reported progress towards 90-90-90 on the Kediri city population in Indonesia was 6.4%-74.9%-9.9%, as reported by Sekalembe et al in 2020 [14]. In Rwanda, a study conducted in 2018 reported 97% of people living with HIV on ART, and 91% of those on ART were virally suppressed [15].…”
Section: Introductionmentioning
confidence: 68%